Decellularization technology in CNS tissue repair. (May 2015) - Wang, Hui; Lin, Xian-Feng; Wang, Li-Ren; Lin, Yi-Qian; Wang, Jiang-Tao; Liu, Wen-Yue; Zhu, Gui-Qi; Braddock, Martin; Zhong, Ming; Zheng, Ming-Hua
Abstract : Decellularization methodologies have been successfully used in a variety of tissue engineering and regenerative technologies and methods of decellularization have been developed for target tissues and organs of interest. The technology to promote regeneration and functional recovery in the CNS, including brain and spinal cord, has, however, made slow progress mainly because the intrinsic regenerative potential of the CNS is regarded as low. To date, currently available therapies have been unable to provide significant functional recovery and successful therapies, which could provide functional restoration to the injured brain and spinal cord are controversial. In this review, the authors provide a critical analysis, comparing the advantages and limitations of the major decellularization methods and considering the effects of these methods upon the biologic scaffold material. The authors also review studies that supplement decellularized grafts with exogenous factors, such as stem cells and growth factors, to both promote and enhance regeneration through decellularized allografts.